The Ocular Toll of Drug Tourism: A Systematic Review and Meta-Analysis of Cannabis and Methamphetamine Impact on Retinal Architecture and Pupillary Dynamics - Fransiska Lavinia Gracella; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita; I Made Ady Wirawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Drug tourism involves individuals traveling across international borders to access recreational illicit substances. While psychiatric and cardiovascular toxicities of substances like cannabis and methamphetamine are established, quantitative data regarding their impact on ocular microstructures and functional dynamics remain scarce. This study aims to systematically review and meta-analyze the structural and functional ocular alterations induced by these substances. Methods: A systematic review and meta-analysis complying with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were conducted. Electronic databases (PubMed, Scopus, Web of Science, Cochrane Library) were searched from inception to January 2026. Data extraction targeted pupillary dynamics and structural optical coherence tomography measurements. Methodological quality was assessed using the Newcastle-Ottawa Scale and Cochrane Risk of Bias tools. A DerSimonian-Laird random-effects model was utilized in Review Manager 5.4 to pool continuous data, calculating Standardized Mean Differences and 95% Confidence Intervals. Heterogeneity was evaluated via the I-squared statistic. Results: Nine primary research articles were included. The mean Newcastle-Ottawa Scale score was 8.1, indicating a low risk of bias. Chronic cannabis users exhibited significantly reduced pupillary constriction velocity (Standardized Mean Difference -0.85, 95% Confidence Interval -1.20 to -0.50, p < 0.001), prolonged reaction latency (Standardized Mean Difference 0.65, 95% Confidence Interval 0.30 to 1.00, p < 0.01), and decreased corneal endothelial cell density (Standardized Mean Difference -0.78, 95% Confidence Interval -1.15 to -0.41, p < 0.001). Methamphetamine abuse was associated with profound global retinal nerve fiber layer thinning (Standardized Mean Difference -1.12, 95% Confidence Interval -1.55 to -0.69, p < 0.001) and reduced minimum rim width (Standardized Mean Difference -0.95, p < 0.001). Conclusion: Recreational cannabis and methamphetamine abuse cause significant, quantifiable ocular morbidity. Methamphetamine induces ischemic neurodegenerative retinal loss, while cannabis disrupts autonomic pupillary pathways and corneal integrity. Comprehensive ophthalmological screening is critical for individuals with substance abuse histories.